Propylthiouracil-induced Alopecia Accompanying Hypohidrosis and Onychomadesis - Nozomi Yanagida; Shunsuke Takahagi; Akio Tanaka; Michihiro Hide (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)